UPAYA MENINGKATKAN KARAKTER MAHASISWA MELALUI KEBIJAKAN PENDIDIKAN - Nurizka, Rian; Lukitoaji, Beny Dwi (Jurnal Civic Hukum, 2019)
This study aims to determine efforts to improve student character through education policy. This type of research is descriptive qualitative research. This research can be classified in the category of field research. Data collection used in this study uses observation, interview, and documentation techniques. Data analysis in this study is data collection, data reduction, data presentation, and conclusion. The results of the study show that the PGSD study program policy in its efforts to improve student character is by character education strategy, namely the development of an educational unit culture through a policy of using uniform and point cards. Co-curricular character education strategy through the activities of the learning media competition festival and the PGSD Award. Extracurricular character education strategy through Scouting and Kepalangmerahan activities. Character values obtained include discipline in dress, culture, love for the homeland, a spirit of national responsibility, active in activities, creative